Synovial synthesis of rheumatoid factors and immune complex constituents in early arthritis. Issue 2 (April 1984) - Jones, V; Taylor, P C; Jacoby, R K; Wallington, T B
Abstract : Synovial synthesis of immune complex constituents and rheumatoid factors has been estimated in rheumatoid arthritis (RA) and in unclassifiable inflammatory arthritis (IA) and related to duration of symptoms. Within 6 months of onset of symptoms both RA and IA patients synthesised (or trapped) immune complexes locally. However, local synthesis of the rheumatoid factors was almost exclusive to RA patients and mainly in patients with symptoms of more than 6 months' duration. Thus all arthritis patients may respond immunologically to an initial trigger in the affected joint but only RA patients develop localised chronic autoimmunity later.